Evaluating route to impact convergence of the harmonic balance method for piecewise-smooth systems - Saunders, B. E.; Kuether, R. J.; Vasconcellos, R. [UNESP]; Abdelkefi, A. (Elsevier, 2023)
In this work, we investigate the applicability of the harmonic balance method (HBM) to predict periodic solutions of a single degree-of-freedom forced Duffing oscillator with freeplay nonlinearity. By studying the route to impact, which refers to a parametric study as the contact stiffness increases from soft to hard, the convergence behavior of the HBM can be understood in terms of the strength of the non-smooth forcing term. HBM results are compared to time-integration results to facilitate an evaluation of the accuracy of nonlinear periodic responses. An additional contribution of this study is to perform convergence and stability analysis specifically for isolas generated by the non-smooth nonlinearity. Residual error analysis is used to determine the approximate number of harmonics required to get results accurate to a given error tolerance. Hill's method and Floquet theory are employed to compute the stability of periodic solutions and identify the types of bifurcations in the system.
Keywords: Convergence analysis; Floquet stability; Harmonic balance; Isolas; Piecewise-smooth